2002
DOI: 10.1103/physreve.66.066303
|View full text |Cite
|
Sign up to set email alerts
|

Realizability of stationary spherically symmetric transonic accretion

Abstract: The spherically symmetric stationary transonic (Bondi) flow is considered a classic example of an accretion flow. This flow, however, is along a separatrix, which is usually not physically realizable. We demonstrate, using a pedagogical example, that it is the dynamics which selects the transonic flow.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 9 publications
2
75
0
Order By: Relevance
“…The separatrices of the saddle point with higher value ofṀ in the polytropic case (with lower value of C in isothermal case) form the homoclinic connection. Physically this is what it has to be, because it is the third critical point (saddle) which will allow the transonic flow solution from infinity to the event horizon, and here, following the line of argument in Ray & Bhattacharjee (2002), it can be stated that the stationary flow solution has to settle on the separatices of a saddle point only. That is why among the critical points, only the saddle points are termed as sonic points, and not the centre-type points, although for both the types of critical points the flow speed is equal to the sound speed, i.e.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separatrices of the saddle point with higher value ofṀ in the polytropic case (with lower value of C in isothermal case) form the homoclinic connection. Physically this is what it has to be, because it is the third critical point (saddle) which will allow the transonic flow solution from infinity to the event horizon, and here, following the line of argument in Ray & Bhattacharjee (2002), it can be stated that the stationary flow solution has to settle on the separatices of a saddle point only. That is why among the critical points, only the saddle points are termed as sonic points, and not the centre-type points, although for both the types of critical points the flow speed is equal to the sound speed, i.e.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…With respect to accretion studies in particular, this kind of parametrisation has been reported before (Ray & Bhattacharjee 2002;Afshordi & Paczyński 2003;Chaudhury et al 2006;Mandal et al 2007;Goswami et al 2007;Bhattacharjee et al 2009b). The critical points have been fixed in terms of the flow constants.…”
Section: Nature Of the Fixed Points : A Dynamical Systems Studymentioning
confidence: 99%
“…The trouble with the transonic solution in the stationary regime is that its realizability is extremely vulnerable to even an infinitesimal deviation from the precisely needed boundary condition to generate the solution [7]. This difficulty may be overcome by considering the temporal evolution of global solutions towards the transonic state [7,8], but there is no analytical formulation to solve the nonlinear partial differential equations governing the temporal evolution of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty may be overcome by considering the temporal evolution of global solutions towards the transonic state [7,8], but there is no analytical formulation to solve the nonlinear partial differential equations governing the temporal evolution of the flow. So, much of all time-dependent studies in spherically symmetric accretion is perturbative and linearized in character, although some non-perturbative studies are also known [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation